Headache with Benign Alternating Hemiplegia - J Gordon Millichap (Pediatric Neurology Briefs, 2004)
An 8-year-old boy with benign familial nocturnal alternating hemiplegia of childhood (BNAHC) and severe headache and vomiting during episodes is reported from the University of Rochester, NY.